Preparing future teachers for work in an inclusive educational environment - Dubovyk, Svitlana H; Lyurina, Tanita I.; Molodychenko, Valentyn V.; Molodychenko, Nataliia A.; Moskalenko, Alla M. (International Journal of Psychosocial Rehabilitation, 2020)
A modern understanding of the essence of integrated learning is that its formation is correlated primarily with an understanding of subjectivity. If to consider the aspect of creating an educational environment that is able to form a stable level of education for children not only with mild abnormalities, but also people with severe antisocial forms of diseases, then the use of integrated education contributes to the formation of a full citizenship and adaptation of minimally professional skills. The novelty of the study is determined by the fact that the formation of pedagogical techniques and methods is based primarily on the necessity to achieve such parameters as the general educational environment and methods for its development. The authors of the article show aspects of the formation of personal levels in integrated education, determine the methods and forms of support for this technology, and summarise the data on sufficient levels for adaptation by both students and educational institutions. The authors show that the use of inclusive education should become a standard teaching pattern in school. The practical significance of the study is determined by the fact that the developed models for the implementation of the general educational space in school will contribute to the overall integration of children in social conditions.